Surto de crescimento médio: correlação entre a estatura, a maturação óssea e a mineralização dentária pelo método radiográfico - Manhães Júnior, Luiz Roberto Coutinho [UNESP] (2004)
The aim of this research is the elaboration of the mid-growth spurt (SCM) curve by distance graphic and the correlation with hand-wrist bone maturation and dental mineralization of lower second molar. The sample is constituted of 193 children's handbooks, being 104 female and 89 male that ages between 72 to 119 months. The division of the handbooks is by sex and eight age groups. The statistical analyses are realized separately for each group and in the finish, are connected to obtain the correlation of the three variables. Considering the height, there aren't differences statistically significant in both sex, but in the graphics are verified the female high peak in SCM is earlier in six months of difference than male. The time of the SCM is 78 to 107 months to female while with male is 84 to 113. Both sex are in the high peak when the epiphyse of the ulnar bone is equal to diaphise. The transition phase between complety crown and begin of the radicular formation in dental mineralization is noted in female and, to male the begin of the radicular formation is observed when both sex in the peak. The conclusion are that to the final of the SCM the female already begin the pubertal growth spurt (SCP), however the male have a latency period of two years approximately